Building Political Identity through Visual Affective Polarisation on Instagram: A Comparison of Six European Far-Right Parties - Zamora-Medina, Rocío; Shahini-Hoxhaj, Remzie; Gërguri, Dren (KOME, 2025)
This article compares the power of visual affective polarisation on Instagram among six European far-right political parties with the aim of enhancing academic knowledge about the manner in which these parties construct their political identity through visual symbols, rhetoric, and imagery to appeal to their target audiences and convey their ideologies. Through quantitative content analysis of Instagram visuals posted on Instagram by the six main European far-right parties during a two-month period, we focused on content-related and format-related variables, as well as technical features, to analyse those visuals as denotative, connotative and ideological systems from the visual framing model perspective. Findings revealed significant differences in the visual framing strategies among these European far-right political parties, pointing to the complexity in identifying a common pattern in their strategic visual communication regarding affective polarisation. This study contributes to the existing literature on visual communication and affective polarisation strategies in politics.